2013
DOI: 10.1063/1.4828496
|View full text |Cite
|
Sign up to set email alerts
|

Graphene nanomesh transistor with high on/off ratio and good saturation behavior

Abstract: We investigate the device operation and performance of transistors based on a graphene nanomesh lattice. By means of numerical simulation, we show that this device architecture allows suppressing the chiral tunneling, which reduces drastically the off current and enhances the on/off ratio compared to the pristine graphene counterpart. Additionally, a good saturation of current can be reached in the thermionic regime of transport. Though reduced compared to the case of pristine transistors, the transconductance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…Graphene nanomesh (GNM), a graphene sheet with periodically arranged nanopores, has attracted extensive attention in recent a few years due to the promising applications in the field-effect transistors [1][2][3][4][5][6][7][8], vapor detection [9][10][11], photothermal therapy [12] and energy storage [13]. GNMs can be viewed as networks of graphene nanoribbons (GNRs), but GNMs have significantly higher on-off ratio and larger supported current than GNRs [1,14]. It has also been shown that GNMs have a strong negative differential conductance which is useful for high frequency applications [15].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene nanomesh (GNM), a graphene sheet with periodically arranged nanopores, has attracted extensive attention in recent a few years due to the promising applications in the field-effect transistors [1][2][3][4][5][6][7][8], vapor detection [9][10][11], photothermal therapy [12] and energy storage [13]. GNMs can be viewed as networks of graphene nanoribbons (GNRs), but GNMs have significantly higher on-off ratio and larger supported current than GNRs [1,14]. It has also been shown that GNMs have a strong negative differential conductance which is useful for high frequency applications [15].…”
Section: Introductionmentioning
confidence: 99%
“…First, it has been shown that by using bilayer graphene instead of single-layer material and applying a perpendicular field, a gap is formed [7,8]. A second option is to create narrow confined graphene structures, such as GNRs (graphene nanoribbon) [9,10] or graphene nanomeshes [11,12], in which a gap opens. In the present work, we focus on GNRs and use these as MOSFET channels.…”
Section: Introductionmentioning
confidence: 99%
“…4a and 4b is caused the saturation current, as is observed for the conductivity behavior of single carbon nanotube and graphene. [22][23][24] In the NCM523 electrode, the electronic conductivity is provided by the carbon black matrix, which has a limit due to its finite amount of free electrons. This limit current provided by the carbon black matrix is defined as a saturation current and its relation to the saturation current of the electrode can be expressed as in Equation 1.…”
Section: Resultsmentioning
confidence: 99%